Emerging Trends in Human Resource Management (HRM) - Kapoor, Mona (Gyan Management Journal, 2016)
In today's turbulent environment, competitive position of any business system within the global environment depends upon its flexibility, inventiveness and focusing on their human capital. The strategic role of human resource management in the era of globalization is becoming imperative to create new, modern and quality human resources that are helpful in accomplishing the goals of business. The management is on the need to search out, establish and utilize competitive advantage for the survival of business. Business organizations are putting greater emphasis on attracting and retaining human capital rather than financial capital. With fast changing world, an urgent need was felt for transforming traditional Human Resource Management {HRMJ. Over the years, there has been a tremendous change in style and substance from personnel management to HRM and recently to International Human Resource Management (IHRM). HRM in global context provides the opportunity to expand the domain of traditional HRM. Globalization of business is necessitating HR approach because today's knowledge economy needs employees to contribute ideas and be engaged in executing the organization's strategy. The purpose of this paper is to investigate and prioritize the emerging trends of HRM and how these trends can be useful in making business competitive. Present paper proposes a conceptual human resource approach from the literature, provides suggestions by integrating traditional HRM to IHRM.
Keywords: HRM; IHRM; HRM Trends; Globalization; Competitiveness